THE CONCEPT OF JUSTICE IN QUR’AN AND HADITH - Aden Rosadi; Syahrul Anwar; Ateng Ruhendi (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2021)
Abstract: This paper tries to explain about the concept of justice both contained in al-Qur’an and hadith. As part of the implementation of Islamic law and the subsystem of national law, the role and position of the (Islamic) judiciary is very strategic and significant. The existence and position of the principles of justice not only lies in the theoretical development through academic studies, but also practically can provide its own color in the implementation of Islamic law in Indonesia. The implementation of the judicial principles is not only a normative individual obligation, but also a collective obligation involving both academics, legal practitioners and the government. Theoretically and practically, the principles of justice embodied in Qur’an and Hadith greatly affect the course of law and justice enforcement through religious court in Indonesia.Abstrak: Tulisan ini mencoba menjelaskan tentang konsep keadilan baik yang tertuang dalam Alquran maupun hadits. Sebagai bagian dari implementasi hukum Islam dan subsistem hukum nasional, peran dan kedudukan lembaga peradilan (Islam) sangat strategis dan signifikan. Keberadaan dan kedudukan asas keadilan tidak hanya terletak pada perkembangan teoritis melalui kajian akademis, tetapi juga secara praktis dapat memberikan warna tersendiri dalam penyelenggaraan syariat Islam di Indonesia. Pelaksanaan prinsip kehakiman bukan hanya kewajiban normatif individu, tetapi juga kewajiban kolektif yang melibatkan akademisi, praktisi hukum, dan pemerintah. Secara teoritis dan praktis, prinsip keadilan yang terkandung dalam Alquran dan Hadits sangat mempengaruhi perjalanan dan implementasi keadilan di Indonesia dalam upaya menegakkan hukum dan keadilan.